Three-dimensional Monte Carlo simulation of bulk fin field effect transistor - 王骏成 杜刚 魏康亮 张兴 刘晓彦 (Chinese physics B, 2012)
In this paper, we investigate the performance of the bulk fin field effect transistor （FinFET） through a three- dimensional （3D） full band Monte Carlo simulator with quantum correction. Several scattering mechanisms, such as the acoustic and optical phonon scattering, the ionized impurity scattering, the impact ionization scattering and the surface roughness scattering are considered in our simulator. The effects of the substrate bias and the surface roughness scattering near the Si/SiO2 interface on the performance of bulk FinFET are mainly discussed in our work. Our results show that the on-current of bulk FinFET is sensitive to the surface roughness and that we can reduce the substrate leakage current by modulating the substrate bias voltage.